Association of family history and survival in patients with colorectal cancer: a pooled analysis of eight epidemiologic studies. (26th March 2018) - Chong, Dawn Q.; Banbury, Barbara L.; Phipps, Amanda I.; Hua, Xinwei; Kocarnik, Jonathan; Peters, Ulrike; Berndt, Sonja I.; Huang, Wen‐Yi; Potter, John D.; Slattery, Martha L.; White, Emily; Campbell, Peter T.; et al.
Abstract: A family history of colorectal cancer (CRC) in first‐degree relatives (FDRs) increases the risk of CRC. However, the influence of family history on survival among CRC patients remains unclear. We conducted a pooled analysis of survival in 5010 incident CRC cases. Cox proportional hazards models were used to estimate the association of family history with overall survival (OS) and CRC‐specific survival (CSS). We also assessed the impact of the number of affected FDRs and age at CRC diagnosis in the affected FDRs on survival. Among CRC cases, 819 (16%) patients reported a family history of CRC. There were 1580 total deaths over a median follow‐up of 4.6 years, of which 1046 (66%) deaths were due to CRC. Having a family history of CRC was not associated with OS [hazard ratio (HR), 1.03; 95% confidence interval (CI), 0.89–1.19] or CSS (HR, 1.13; 95% CI, 0.95–1.36)]. There were no associations between the number of affected relatives or age at CRC diagnosis of the affected relative with survival (all P trend > 0.05). However, a family history of CRC did confer worse CSS in patients diagnosed with distal colon cancer (HR, 1.45, 95% CI, 1.03–2.04). A family history of CRC was generally not associated with survival after CRC diagnosis. However, having a family history of CRC was associated with worse CRC prognosis in individuals with distal colon cancer, suggesting a possible genetic predisposition with distinct pathogenic mechanism that may lead to worse survival in this group. Abstract : In a pooled analysis of 5010 patients with colorectal cancer (CRC), having a family history of CRC in first‐degree relatives was not associated with overall survival [hazard ratio (HR), 1.03; 95% confidence interval (CI), 0.89–1.19] or CRC‐specific survival (CSS) [HR, 1.13; 95% CI, 0.95–1.36]. However, having a family history of CRC was associated with worse CSS in patients with distal colon cancer (HR, 1.45; 95% CI, 1.03–2.04), suggesting a possible genetic predisposition with distinct pathogenic mechanism that may lead to worse survival in this group.